Holocene evolution of the wave-dominated embayed Moruya coastline, southeastern Australia: Sediment sources, transport rates and alongshore interconnectivity. (1st November 2020) - Oliver, Thomas S.N.; Tamura, Toru; Brooke, Brendan P.; Short, Andrew D.; Kinsela, Michael A.; Woodroffe, Colin D.; Thom, Bruce G.
Abstract: Sediment budgets on wave-dominated coastlines are important in determining shoreline behaviour and are primarily inherited from geological-scale coastal evolutionary history. Sediment compartments provide a framework to conceptualise and investigate sediment budgets over a range of time and space scales. This study aims to assess the sediment budget for a secondary coastal compartment on the New South Wales (NSW) south coast ∼26 km in length and containing five adjacent but discrete Holocene coastal bay barriers: Barlings Beach, Broulee Beach, Bengello Beach, Moruya Heads Beach and Pedro Beach. Building on earlier morphostratigraphic studies, a new series of Optically Stimulated Luminescence (OSL) ages are presented for foredune ridge sequences at previously un-dated sites. Additional Ground Penetrating Radar (GPR) transects complement earlier stratigraphic datasets, and seamless topographic and bathymetric LiDAR datasets provide insight into subaerial coastal deposits and inner shelf morphology in this region. The results demonstrate that barriers within the compartment have two different sediment sources. The barriers are dominated by shoreface supply of quartz-rich sand transported onshore as shoreface morphology evolved towards equilibrium. Skeletal carbonate sand became an important component of the sediment budget for the northern Barlings and Broulee beaches after ∼3000 years ago. Shoreline progradation at Bengello Beach has been steady throughout the mid-to late- Holocene. Bengello contains the largest volume of Holocene sand and accreted at an average rate of 3.1 m 3 /m/yr (for the current shoreline length). The other barrier systems have experienced changes in sediment accumulation rate as their shorelines prograded seaward resulting in changes to their alongshore interconnectivity. Rapid filling of the Pedro Beach embayment by ∼4000 years ago initiated headland bypassing and northward sand transport to Moruya Heads Beach which only then commenced progradation. In contrast, as Broulee and Bengello Beaches prograded they converged in the lee of Broulee Island forming a tombolo which led to division of the former continuous shoreline into two. A marked increase in skeletal carbonate content at Broulee occurred after this separation attesting to the restriction of the southern quartz-sand source replaced by local carbonate production. This study emphasises the importance of understanding the long-term temporal variability in sediment budget and embayment interconnectivity in determining shoreline response to changing boundary conditions such as sea level and wave climate as well as contemporary anthropogenic influences. Highlights: Radiocarbon and OSL dating constrain Holocene barrier evolution Neighbouring barriers have evolved differently according to differing sand sources. Shoreface disequilibrium is an important sand sourcepromoting progradation. Alongshore interconnectivity has changed as embayments infilled.